The Teacher Challenges in Implementing Educational Evaluation Assessment Standards in the Affective Domain at Pondok Mutiara Quran Putri Wonogiri - Inda Rahayu Rayni (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2024)
Teacher challenges in implementing educational evaluation assessment standards in the affective domain is an important issue that needs attention. This study aims to determine how teachers implement educational evaluation standards in the affective realm at Pondok Mutiara Quran Putri Wonogiri. This research method uses qualitative descriptive analysis with a phenomenological approach so as to produce data conclusions to answer problems related to this title. The results of this study show that some of the difficulties faced by teachers in implementing educational evaluation assessment standards. Efforts to improve the implementation of affective education evaluation assessment standards include comprehensive approaches, such as teacher skill development, awareness raising about authentic assessment, and training on data collection techniques